Evaluasi ergonomic di lingkungan kerja perkantoran dan dampaknya terhadap Kesehatan - septian hadi Susetyo (ITB Journal Publisher, LPPM ITB, 2021)
Office work is one of the most common jobs in Indonesia. There are various health risks, especially if it is not in accordance with the worker's body position with tables and chairs. This study aims to evaluate the ergonomics of the office work environment that affect health. This research method by conducting field observations and interviews. Field observations by directly observing the object under study, while interviews were conducted by conducting direct questions and answers with workers. This study resulted in the comfort of chairs and work desks not being directly proportional to health. The highest health complaints occurred in the neck with a contribution of 22.73% followed by the back and hips with a contribution of 18.18% and 15.91%, respectively. In addition, as many as 50% of workers feel that their work performance has decreased due to available tables and chairs.